2011
DOI: 10.1126/science.1201061
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Orbital Currents in CuO

Abstract: Orbital currents are proposed to be the order parameter of the pseudo-gap phase of cuprate high-temperature superconductors. We used resonant x-ray diffraction to observe orbital currents in a copper-oxygen plaquette, the basic building block of cuprate superconductors. The confirmation of the existence of orbital currents is an important step toward the understanding of the cuprates as well as materials lacking inversion symmetry, such as magnetically induced multiferroics. Although observed in the antiferrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 16 publications
8
121
1
Order By: Relevance
“…Therefore, critical difference of the optical response from this work suggests that the character of the optical ME effect strongly depends on their microscopic mechanism beyond simple estimation based on the symmetry. The ME effect implies the possible toroidal moment or its excitation, which stems from the spin orders or orbital currents in some cases 42,43 . The electromagnon observed here may be viewed as the excitation of the toroidal moment, because the toroidal moment is always anticipated under the presence of the crosscoupled DP x and DM x , that is, the dynamical ME effect 21,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, critical difference of the optical response from this work suggests that the character of the optical ME effect strongly depends on their microscopic mechanism beyond simple estimation based on the symmetry. The ME effect implies the possible toroidal moment or its excitation, which stems from the spin orders or orbital currents in some cases 42,43 . The electromagnon observed here may be viewed as the excitation of the toroidal moment, because the toroidal moment is always anticipated under the presence of the crosscoupled DP x and DM x , that is, the dynamical ME effect 21,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Materials whose orbitals possess neither symmetry are said to be magnetoelectric as they play a major role in magnetoelectric phenomena. Of particular interest are toroidal moments, corresponding to time-and parity-odd vectors, that not only play a vital role in magnetoelectric phenomena (Spaldin et al, 2008) but have been suggested to be implicated in high-T c superconductivity (Scagnoli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The study of magnetism in this simple model compound can also have important implications for the understanding of high-temperature superconductors, to which CuO is chemically and structurally related. An experiment performed at the ESRF and at the Swiss Light Source by Scagnoli et al [41], but with a crucial theory contribution from Diamond scientists, seems to show evidence of such a link. Scagnoli et al used resonant X-ray diffraction to observe the so-called orbital currents in a copper-oxygen plaquette, the basic building block of cuprate superconductors.…”
Section: (C) Type II Multiferroicsmentioning
confidence: 99%